2020
DOI: 10.3390/biology9100315
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Responses, Reproduction Mode and Epigenetic Patterns under Temperature Treatments in the Alpine Plant Species Ranunculus kuepferi (Ranunculaceae)

Abstract: Plant life in alpine habitats is shaped by harsh abiotic conditions and cold climates. Phenotypic variation of morphological characters and reproduction can be influenced by temperature stress. Nevertheless, little is known about the performance of different cytotypes under cold stress and how epigenetic patterns could relate to phenotypic variation. Ranunculus kuepferi, a perennial alpine plant, served as a model system for testing the effect of cold stress on phenotypic plasticity, reproduction mode, and epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 122 publications
(215 reference statements)
0
19
1
Order By: Relevance
“…Although facultative apomixis restricts recombination and reduces the evolutionary potential of the species, it maintains the fertility of individuals and is advantageous for colonization [ 56 ]. Apomixis could also support the fitness of a population under unfavorable environmental conditions [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although facultative apomixis restricts recombination and reduces the evolutionary potential of the species, it maintains the fertility of individuals and is advantageous for colonization [ 56 ]. Apomixis could also support the fitness of a population under unfavorable environmental conditions [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, global methylation analysis in facultative diplosporous Eragrostis curvula revealed that variations in apomixis/sexual expression, produced either overtime or by stress conditions, came along with epigenetic modifications [45,46]. Exploration of Cytosine methylation patterns in di-and tetraploid cytotypes and in different reproduction modes of Ranunculus kuepferi suggest that, in addition to the confirmed correlation of methylation profiles with the ploidy level, a causal relationship exists between methylation patterns and the mode of reproduction [47,48]. A recent comparative analysis between sexual and apomictic floral sRNA components of P. notatum detected significant differences associated with the reproductive mode, including auxin metabolism, transport and signaling [49].…”
Section: Introductionmentioning
confidence: 95%
“…Antioxidant defense systems were activated to support heat tolerance sufficiently in Dioscorea and Arabidopsis [71,72]. Chromosomal abnormality plants might be tolerance of cold stress via growing antioxidant and epigenetic [73,74]. Changing root anatomical characters…”
Section: Chromosomal Abnormality Enhances Abiotic and Biotic Tolerancementioning
confidence: 99%